PENGARUH STRUKTUR KEPEMILIKAN DAN KOMITE AUDIT TERHADAP MANAJEMEN LABA - Luluk Yumna Noor Farida; Rr. Karlina Aprilia Kusumadewi (Diponegoro Journal of Accounting, 2019)
The purpose of this research is to examine whether ownership structure and audit committee influences earnings management. The independent variables used in the research are managerial ownerhsip, institutional ownership, foreign ownership, and audit committee. Meanwhile, the dependent variable in the research is earnings management. This research uses regresion analysis method with secondary data obtained based on a sampling method, and that is purposive sampling, so that 48 samples of manufactured company in Indonesia was obtained. The resulf of this study indicate that managerial ownership does not have a significant influence on earnings management, institutional ownership has a negative effect on earnings management, family ownership has a negative effect on earnings management, and foreign ownership does not have a significant influence on earnings management. Furthermore, audit committee is proven does not have a significant influence on earnings management too.